A role of statins against listeria monocytogenes and Mycobacterium tuberculosis infection - Parihar, Suraj P (Division of Immunology, 2015)
Cholesterol has been shown to play important role in the pathogenesis and persistence of intracellular pathogens. Here, we modulate host cholesterol biosynthesis pathway using pharmacological agent statins, which are reversible inhibitors of HMGâ€ CoA reductase enzyme. The aim of the study was to investigate the role of statins in inducing host protective responses against intracellular pathogens. We report reduced growth of Listeria monocytogenes (LM) and Mycobacterium tuberculosis (Mtb) in murine macrophages. We show prominent immunomodulatory activity induced by statins, mainly increased phagosomal maturation and autophagy resulting in decreased bacterial growth in macrophages. Subsequently, statinâ€ treated mice showed decrease in bacterial loads, accompanied by reduced histopathology in the acute phase of infection during listeriosis and tuberculosis. Furthermore, we found decreased growth of Mtb in peripheral blood mononuclear cells (PBMC) and monocyteâ€ derived macrophages (MDM) isolated from patients with familial hypercholesterolemia (FH) on statin therapy when compared to healthy subjects. Together, our results show that statins induces protection against Mtb in murine macrophages, mice and human mononuclear cells and monocyteâ€ derived macrophages.